2020
DOI: 10.7150/ijms.45842
|View full text |Cite
|
Sign up to set email alerts
|

Tert-butylhydroquinone mitigates Carbon Tetrachloride induced Hepatic Injury in mice

Abstract: Tert-butylhydroquinone (tBHQ) is an antioxidant compound that exhibits cytoprotective effect in many tissues under pathological condition. However, its role in carbon tetrachloride (CCL4) induced liver injury is still unclear. Here we established a carbon tetrachloride induced hepatic injury model in mice to determine whether tBHQ can mitigate CCL4 induced liver damage. In our study, we found tBHQ exhibited protective effects in CCL4 treated mice model. TBHQ markedly improved hepatic function and decreased hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Nevertheless, cell damage occurs when cells encounter excessive oxidative stimulation that exceeds the capacity of the antioxidant defense system. The excessive oxidative stimulus will cause the oxidization of the cell's membrane and eventually destroy cells ( Li et al, 2020b ). It has been reported that the reduction of oxidative stress plays a pivotal role in diminishing hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, cell damage occurs when cells encounter excessive oxidative stimulation that exceeds the capacity of the antioxidant defense system. The excessive oxidative stimulus will cause the oxidization of the cell's membrane and eventually destroy cells ( Li et al, 2020b ). It has been reported that the reduction of oxidative stress plays a pivotal role in diminishing hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Acute liver failure (ALF) is a critical clinical syndrome that leads to high mortality in clinic [ 1 ]. Pathogenic factors such as viral infection, toxic chemicals, and hepatotoxic drugs can cause ALF [ 2 5 ]. Lipopolysaccharide (LPS) is a component of the outer cell wall of gram-negative bacteria, which can induce liver damage by activating inflammatory cytokine production [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, hepatocytes are protected from oxidative injury by antioxidative enzymes in the liver. Many antioxidative genes are regulated by Nrf2, and activation of Nrf2 shows a protective effect in hepatic diseases [ 5 , 11 , 12 ]. Normally, Nrf2 is combined with Kelch-like ECH2-associated protein 1 (Keap1) in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if 5-CMF and its GSH conjugate are exported by different rates, then compounds that alter cytoplasmic GSH levels, for example, by conjugating to GSH, may influence the results of the CMFDA assay. Therefore, we used two compounds that have been reported to alter intracellular GSH levels, DLbuthionine-sulfoximine (BSO), an inhibitor of gamma-glutamylcysteine synthetase [28], the rate limiting enzyme in GSH synthesis, and the NRF2 activator tert-butylhydroquinone (TBHQ) [29]. Incubations with BSO and TBHQ were performed for 48 h prior to the CMFDA assay.…”
Section: No Influence Of Substances That Deplete or Induce Glutathione Levelsmentioning
confidence: 99%